The Influence of Career Development on the Performance of Gowa Regency Ministry of Religion Employees - St. Aisya; Muhammad Yusuf; Irwan Abdullah (Pustaka Digital Indonesia, 2024)
This research is a type of quantitative research to determine the influence of career development on the performance of employees of the Ministry of Religion, Gowa Regency. The type of research used is a quantitative analysis by collecting observation data and questionnaires with 64 respondents using validation and reliability test data collection techniques, classical assumption tests, and simple regression analysis. Based on the t-test results, career development shows a sig value smaller than the significance level (0.005 < 0.05), or the t-count value is greater than the t-table (2.915 > 1.671) meaning that career development has a positive and significant effect on employee performance. Based on the results of research conducted at the data collection, data management, and data analysis stages of the influence of career development on the performance of Gowa Regency Ministry of Religion employees, it can be concluded that career development has a positive and significant effect on the performance of Gowa Regency Ministry of Religion employees.